2020
DOI: 10.2147/ppa.s251635
|View full text |Cite
|
Sign up to set email alerts
|

<p>Maternal Satisfaction with Delivery Services of Government Hospitals in Ambo Town, West Shoa Zone, Oromia Region, Ethiopia, 2020</p>

Abstract: Background Maternal satisfaction with delivery service is used to measure the ability of services provided to meet consumers’ expectations. Satisfying women with the care given during labor and delivery helps to develop a positive childbirth experience and a favorable attitude towards motherhood. There were limited studies that assessed maternal satisfaction in Ethiopia, and this study aimed to assess delivery service satisfaction and its associated factors among mothers who gave birth at public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 19 publications
4
22
1
Order By: Relevance
“…The research samples were small, and the type of hospital was relatively monotonous. 1,3,10,25 Based on these deficiencies. This study had improved the survey content and used statistical description, single-factor analysis, and multi-factor analysis to determine the factors that had a greater impact on satisfaction in patient characteristics.…”
Section: Socio-demographic Characteristics That Have Influence On Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research samples were small, and the type of hospital was relatively monotonous. 1,3,10,25 Based on these deficiencies. This study had improved the survey content and used statistical description, single-factor analysis, and multi-factor analysis to determine the factors that had a greater impact on satisfaction in patient characteristics.…”
Section: Socio-demographic Characteristics That Have Influence On Satisfactionmentioning
confidence: 99%
“…The research of Senait and Teshome showed that the assessment of patient satisfaction currently had ambiguous results due to differences between individual factors. 9,10 Miriam's research showed that the subjectivity of patients will affect the results of satisfaction evaluation. 11 The abovementioned studies were used to evaluate the satisfaction of specific types of subjects in the hospital environment of different developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal health complications and lack of prenatal outcomes are often associated with other factors like the non-utilization of antenatal and childbirth services and poor socioeconomic status. Unwanted outcomes are, seen in those mothers who have not done ANC registration due to their delay of antenatal care because of dissatisfaction toward the quality of service pregnant mothers are affected by complications like: preeclampsia, malaria, lack of birth readiness, post-partum hemorrhage due to lack of risk identification at ANC level ( 17 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopian studies conducted in Addis Ababa, Amhara Referral Hospitals, Ambo government hospitals, Hawassa city public hospitals reported that maternal satisfaction with delivery service is 63%, 61.9%, 83.9%, 87.7% respectively (5,9,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Satis ed women with the care given during labor and delivery helps to develop a positive childbirth experience and a favorable attitude towards mother hood but a negative birth experience can make the woman feel distraught and have a negative impact on her mental health, which increases the risks of postpartum blue, depression, psychotic disorders and post-traumatic stress disorder (9) Maternal satisfaction with delivery services varies across countries. Studies conducted in India, Bangladesh, Australia showed that 89.8%, 92.3% and 86.1% of mothers were satis ed with delivery service respectively (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%